Biodegradable triboelectric nanogenerator as a implantable power source for embedded medicine devices - Gang Jian; Shangtao Zhu; Xiao Yuan; Shengqiao Fu; Ning Yang; Chao Yan; Xu Wang; Ching-Ping Wong (NPG Asia Materials)
Abstract Implantable medical devices have played an important role in human medicine in recent decades. However, traditional implanted devices require battery replacement and a second surgery for device removal, which can cause pain to the patient. This work presents a biodegradable triboelectric nanogenerator (BI-TENG) made from both natural and synthetic biodegradable materials that is utilized to collect mechanical energy in vivo and transduce it into electricity. Reed film and polylactic acid were chosen among different biodegradable materials as the triboelectric layers due to having the best generator output performance by providing voltages that reached 368 V. The biocompatibility of the friction layer and the device was verified via a blood test. After implantation in mice, the BI-TENG exhibited an open-circuit voltage of 0.176 V and a short-circuit current of 192 nA as generated from body movement. The BI-TENG was connected to an interdigital electrode to generate an electric field, which stimulated the accelerated release of doxorubicin (DOX) from red blood cells in targeted drug delivery systems. After stopping the electric field, the release of DOX normalized, facilitating the precise killing of cancer cells. Our work demonstrates the broad potential of BI-TENGs in the field of cancer treatment.